Ethnotheology Studies Concerning the Substance of Folk Religion as Local Theology of the Tugutil Ethnic in Halmahera Towards Contextual Ministry - Marde Christian Stenly Mawikere; Sudiria Hura; Imbran Batelemba Bonde (Sekolah Tinggi Theologia Jaffray, 2022)
This article is an ethnotheological study of the substance of Folk Religion as Local Theology of the Tugutil Ethnic in Halmahera Island, North Maluku Province, Indonesia. This study examines and describes the elements of folk religion, namely beliefs about God, humans, sin and salvation as the fundamental beliefs of traditional societies with animism-dynamism patterns. The research was carried out using a qualitative method with an ethnographic approach. The results of this study show that the local theology of the Tugutil ethnicity regarding Jou Ma Dutu as God. He was the creator and owner of the universe; trichotomous human nature o roehe-o gikiri-o gurumini; the human reality that is o baradoha ma nyawa which only causes the instability of the universe and disturbances to the ancestral spirits. Likewise, the concept of salvation they believe in is present and pragmatic, which does not give place to futuristic eternal life. The final result of this study shows that by examining deeply folk religion, the local theology was adopted by the Tugutil ethnic group. It becomes a consideration for implementing sociocultural approaches and contextual ministry, both spiritual and social ministry, for the Tugutil ethnic group as one of the isolated community groups in Indonesia.